Muze als Motor II : Beeldende kunst in Brabant 1945-1996. - Berndes, Christiane; Debbaut, Jan; Driessen, Hendrik; Franssen, Diana; Goedegebuure, Jaap; Guldemond, Jaap; Heezen, Henriëtte; Herst, Sonja; Klein Essink, Selma; Koelman, Wouter; Lubbers, Frank; Meulenbroek, Désirée; et al. (Breda : De Beyerd Breda, 1996)
Adriaans, Léon ; Arink, Karin ; Atelier van Lieshout ; van Bakel, Gerrit ; Berkulin, Arie ; Besems, Korrie ; Biezen, Hans ; Birza, Rob ; Bol, Kees ; Claassen, Johan ; Claassen, Tom ; Daniëls, Remi ; Dirkx, Piet ; Van Eyk, Jan ; van Eyk, Ria ; Fortuyn/O'Brien ; Frenken, Jacques ; Geelen, Guido ; Gregoor, Jan ; Hocks, Teun ; van Hoek, Hans ; Horvers, Toine ; Jacobs, Henri ; Kantelberg, Peter ; de Kemp, Tamar ; Kooijmans, Jolanda ; Körmeling, John ; Korsmit, George ; de Kroon, Harrie ; Kuypers, Theo ; Lamers, Kiki ; Lennarts, Johan ; Leyendeckers, Hubert ; van der Linden, Thomas ; Lippens, Guido ; Loerakker, Bert ; Manders, Jos ; Martinali, Willi ; van Melis, Jan Hein ; Mol, Kees ; Mol, Pieter Laurens ; Mulders, Marc ; Nagtzaam, Marc ; Nies, Jean ; de Nooijer, Paul ; Panhuysen, Paul ; Peeters, Sef ; Persoon, Kars ; Peulen, Martin ; Popma, Carola ; van Riessen, Wouter ; Roosen, Maria ; Sanders, Pim-Martijn ; van Schaijk, Mieke ; Snijders, Ad ; Soons, Mariëlle ; Steenbergen, Niel ; Strik, Elly ; Theuws, Roos ; Toebosch, Moniek ; Vanderheyden, JCJ ; Veneman, Peer ; Verdult, Dick ; Vermeule, Koen ; Vermeulen, Alex ; Versloot, Ronald ; Visch, Henk ; de Vries, Jaap ; de Weyer, Tine van ; de Wit, Hans ; Zwartjes, Frans
biog. p. 193-195
Nederlands
De Muze als Motor II : Beeldende Kunst in Brabant 1945-1996, De Beyerd, Breda, 14.10 - 24.11.1996 ; De Pont, Tilburg, 14.09 - 01.12.1996 ; Van Abbemuseum, Eindhoven, 14.09 - 01.11.1996
kunstcatalogus
Keywords: Brabant; Nederland